Sensitization to gliadin induces moderate enteropathy and insulitis in nonobese diabetic-DQ8 mice - Galipeau, Heather J. (2011)
Celiac disease (CD) is frequently diagnosed in patients with type 1 diabetes (T1D), and T1D patients can exhibit Abs against tissue transglutaminase, the auto-antigen in CD. Thus, gliadin, the trigger in CD, has been suggested to have a role in T1D pathogenesis. The objective of this study was to investigate whether gliadin contributes to enteropathy and insulitis in NOD-DQ8 mice, an animal model that does not spontaneously develop T1D. Gliadin-sensitized NOD-DQ8 mice developed moderate enteropathy, intraepithelial lymphocytosis, and barrier dysfunction, but not insulitis. Administration of anti-CD25 mAbs before gliadin-sensitization induced partial depletion of CD25+Foxp3+ T cells and led to severe insulitis, but did not exacerbate mucosal dysfunction. CD4+T cells isolated from pancreatic lymph nodes of mice that developed insulitis showed increased proliferation and proinflammatory cytokines after incubation with gliadin but not with BSA. CD4+ T cells isolated from nonsensitized controls did not response to gliadin or BSA. In conclusion, gliadin sensitization induced moderate enteropathy in NOD-DQ8 mice. However, insulitis development required gliadin-sensitization and partial systemic depletion of CD25+Foxp3+ T cells. This humanized murine model provides a mechanistic link to explain how the mucosal intolerance to a dietary protein can lead to insulitis in the presence of partial regulatory T cell deficiency.